THE ROLE OF THE UNITED NATIONS IN PEACEKEEPING AND THE IMPACT OF INTERNATIONAL INVESTMENTS AND ECONOMIC SANCTIONS ON THE ISRAEL-PALESTINE AND RUSSIA-UKRAINE CONFLICTS (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the role of the United Nations in peacekeeping, as well as the impact of international investments and economic sanctions on the Israel-Palestine and Russia-Ukraine conflicts. It discusses UN peacekeeping missions, their effectiveness, and practical limitations. Furthermore, the article explores the deterioration of the investment climate due to the conflicts and examines both the positive and negative consequences of sanctions. Through these analyses, the role of economic and diplomatic tools in conflict resolution is highlighted, along with their importance for global security.